Ultra-sensitive dengue NS1 protein detection via asymmetric source-drain, heterojunction and dual-dielectric cavities in a uniform tunnel FET biosensor - Ranjith Kumar T; Lakshmi Priya G (Results in Engineering)
In this paper, we present a unique Asymmetric Source-Drain Heterojunction Dual-Dielectric Uniform Tunnel Field Effect Transistor (A-SD-HJ-DD-UTFET) based biosensor tailored for the early detection of dengue NS1 protein during the acute phase of infection offering early diagnosis and potentially life-saving intervention. The proposed biosensor design features simplified fabrication, a narrow drain region, and a dual material control gate, enhancing specificity and sensitivity for dengue virus detection. Using a heterojunction configuration, this device optimizes electron flow for improved detection accuracy. The roles of Tunnel Gate (TG) and Auxiliary Gate (AG) are studied in terms of band energy, electric field, electrostatic potential, and other sensitivity parameters. Sentaurus TCAD tool is utilized for analyzing the characteristics of the proposed A-SD-HJ-DD-UTFET biosensor. Simulation results indicate that the designed A-SD-HJ-DD-UTFET biosensor achieves a superior Subthreshold Swing (SS) of 15.4 mV/dec and an enhanced ION/IOFF sensitivity of about 2.25 × 10¹¹ with a maximum ON and minimum OFF state currents of 2.28 × 10–4 A/μm and 1.28 × 10–16 A/μm respectively for detecting NS1 protein of dengue. Additionally, it boasts a high switch ratio in the order of 1012. The proposed biosensor outperforms conventional devices, including the state-of-the-art Junctionless (JL)-TFET biosensors. The superior electrical characteristics of the proposed A-SD-HJ-DD-UTFET biosensor make it a promising device for early detection of the dengue NS1 protein, providing a potent solution for mitigating the spread of dengue infections.